2012
DOI: 10.1016/j.is.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

An ontology-based retrieval system using semantic indexing

Abstract: , 57 pages In this thesis, we present an ontology-based information extraction and retrieval system and its application to soccer domain. In general, we deal with three issues in semantic search, namely, usability, scalability and retrieval performance. We propose a keyword-based semantic retrieval approach. The performance of the system is improved considerably using domain-specific information extraction, inference and rules. Scalability is achieved by adapting a semantic indexing approach. The system is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Performance of the system is improved when compared to Traditional Search. Kara et al (2010) were not able to achieve the 100% precision and recall values.…”
Section: Semantic Indexingmentioning
confidence: 89%
“…Performance of the system is improved when compared to Traditional Search. Kara et al (2010) were not able to achieve the 100% precision and recall values.…”
Section: Semantic Indexingmentioning
confidence: 89%
“…With respect to the shortcomings of traditional citation information services, the introduction of ontology may help users to improve their searches aimed at multiple citation retrieval. In 2012, Kara, Alan, Sabuncu, Akpınar, Cicekli, and Alpaslan [18] found that while thesauruses are concerned with meanings at the level of words, ontologies more specifically deal with meanings at the level of real-world entities denoted by words. That is, ontologies deal with the interpretation of words in terms of real-world entities.…”
Section: Related Workmentioning
confidence: 99%
“…In (Kara et al, 2012), an information extraction system based on ontology and recovering systems and their applications in football environment was presented. In general, this work comprises three subjects in semantic searching: usage facility, scalability and facility of recovery.…”
Section: Review Of Literaturementioning
confidence: 99%